The Effectiveness of Clinical Breast Examination (Sadanis) Application to Breast Self Examination (BSE) in Pemalang - Mei Zumaro, Elqy; Laksono, Budi (Public Health Perspective Journal, 2019)
Breast cancer is one of the causes of female deaths in Indonesia. It is estimated that 50% of breast cancer sufferers in Indonesia come to have their disease checked at an advanced stage. Self Breast Examination (BSE) is a good first step to find out if there is breast cancer as early as possible, the delay in early detection is likely due to a lack of knowledge of early breast cancer detection. The purpose of this study was to determine the effectiveness of Clinical Breast Examination (SADANIS) on Self Breast Examination (BSE) behavior in Pemalang in 2017. The design in this study was Cross-sectional, conducted in December 2017. The population of this study were 149 women who had implemented SADANIS from May to August 2017 in the work area of Kabunan Health Center in Pemalang Regency, with a sample of 78 respondents who met the inclusion criteria. The results showed that the majority of the study respondents had a very agreeable attitude of 76%, 85% of respondents had good knowledge. % of respondents apply their own breast examination (BSE) every month after menstruation, there is a relationship between the attitude of respondents to the implementation of self breast examination (BSE) (p. 0.002), there is a relationship between the respondents' knowledge of the application of breast self examination (BSE) (p. 0.002), very much variable influence on breast self-examination (BSE) in Pemalang 2017 is the attitude of the respondent (p 0.017) and the respondent's knowledge of the application of breast self-examination (BSE) is 0.024.